Analisis Pusat Pertanggungjawaban Pusat Kos dan Evaluasi Kinerja pada Pabrik Tahu UD. Sumber Makmur Bangkalan - Hasma Diana Yulia; Rahma Suro Anjani; Yulia Wulandari; Fina Silviyah; Ahmad Ahmad; Mochamad Reza Adiyanto (Universitas 45 Surabaya, 2025)
This study aims to design an accountability report that can be the basis for measuring performance for UD. Sumber Makmur, which previously did not have such a system. This research uses descriptive quantitative research methods. The data collection techniques used in this study include in-depth interviews and documentation to collect data related to organizational structure, performance evaluation, and company financial reports for the period 2022-2023. Analysis was conducted using variance calculations between budget and actual costs, and using Return on Investment (ROI) ratios to evaluate performance. The findings show that the implementation of accountability reports and performance evaluation at UD. Sumber Makmur is still not going well. The company has not prepared a detailed cost budget for each department, which has led to inefficiencies in spending and using resources including a significant decrease in net profit in some periods, unfavorable cost variances, and low Return on Investment (ROI). This study has limitations in that it only focuses on one company, so the results may not be generalizable to all SMEs. SMEs need to implement a more detailed accounting system, budgeting by department, and transparent performance evaluation. These steps can improve the company's cost efficiency, profitability, and competitiveness in the market.